Multiple resonance thermal activation delayed fluorescence material based on long and short axis hybridization and its application in organic electroluminescent devices

CN122978162APending Publication Date: 2026-10-27JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611203988.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-10
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

但是与具有长程电荷转移(long-range charge transfer,LRCT)的传统TADF相比,MR-TADF材料往往由于较大的与小的单重态-三重态旋轨耦合(spin-orbit coupling,SOC)呈现较慢的反向系间窜越速率(kRISC为103-104 s-1)

Benefits of technology

[0017]针对现有MR-TADF材料在OLED应用中普遍存在的聚集诱导淬灭、高亮度下效率滚降严重以及色纯度与反向系间窜越(RISC)速率难以兼顾等问题,本发明提出一种“双短轴-长轴辅助电荷转移”策略,旨在不牺牲色纯度的前提下显著加快RISC过程。该策略的核心是在经典多重共振(MR)骨架中,于吲哚并咔唑桥上引入具有适当位阻的给受体型长程电荷转移单元,使分子同时具备短程电荷转移(SR-CT)、空间电荷转移(TS-CT)以及长程电荷转移(LR-CT)多重激发态特征。通过调节受体与中性基团的强度,可额外构建TS-CT和LR-CT辅助通道,有效减小单重态-三重态能隙(),增强自旋-轨道耦合,从而大幅促进三线态激子向单线态的上转换。同时,扭曲的分子构象能够有效限制分子内振动弛豫,抑制聚集态下的非辐射猝灭;而保留的MR-TADF骨架中的SR-CT组分则确保了高荧光量子产率和极窄的发射半峰宽。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978162A_ABST
    Figure CN122978162A_ABST
Patent Text Reader

Abstract

A multiple resonance thermal activation delayed fluorescence material based on long and short axis hybrid and application thereof in an organic electroluminescent device belong to the technical field of organic electroluminescent device.The present application proposes a "double short axis-long axis auxiliary charge transfer" strategy, which aims to significantly accelerate the RISC process without sacrificing color purity. The core of the strategy is to introduce a donor-acceptor type long-range charge transfer unit with appropriate steric hindrance on the indolocarbazole bridge in the classic multiple resonance (MR) skeleton, so that the molecule has the characteristics of short-range charge transfer (SR-CT), space charge transfer (TS-CT) and long-range charge transfer (LR-CT) multiple excited state, greatly promotes the upconversion of triplet excitons to singlet, significantly alleviates the efficiency roll-off and half-peak width widening problems commonly seen in traditional MR-TADF devices, and the color purity is not negatively affected, which has important value for the further popularization and commercial application of organic electroluminescent technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of organic electroluminescent device technology, specifically relating to a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization and its application in organic electroluminescent devices. Background Technology

[0002] Organic light-emitting diodes (OLEDs) are a novel display technology. Due to their advantages such as high brightness, fast response, wide viewing angle, simple manufacturing process, and flexibility, they have made significant progress in full-color display and lighting applications, becoming a current hot trend in industrialization. In recent years, luminescent materials based on the thermally-activated delayed fluorescence (TADF) mechanism have been widely used in OLED luminescence, becoming a cutting-edge research hotspot in the field of luminescent materials. This is because they can achieve efficient utilization of triplet excitons (theoretically 100%) through the reverse intersystem crossing (RISC) process from the T1 state to the S1 state.

[0003] However, most traditional TADF materials often employ a distorted donor-acceptor (DA) structure. With increasing HOMO-LUMO separation, the oscillator strength (f) of the TADF material decreases significantly, thereby reducing the fluorescence quantum yield (PLQY). Simultaneously, the vibrational relaxation and ground-excited state coupling significantly broaden the emission full-width at half maximum (FWHM > 70 nm), failing to meet the high efficiency and high color purity requirements of full-color display technology. Although device structures using filters and microlens arrays (MLAs) can meet the color purity requirements of displays and improve the external quantum efficiency (EQE), they often require complex device structures, leading to energy loss and hindering the energy-saving and environmentally friendly requirements of green chemistry.

[0004] In 2016, Hatakeyama proposed a design strategy for narrowband TADF materials with multiple resonance (MR) effects (MR-TADF). Electron-donating atoms (N) are regularly arranged in adjacent positions relative to electron-withdrawing atoms (B) in the fused polycyclic aromatic skeleton. Without constructing a distorted DA structure, high PLQY and minimized molecular structural relaxation and vibrational coupling are achieved through a unique short-range charge transfer (SRCT). This design strategy gives the material excellent properties such as small Stokes shift, narrow emission spectrum, and extremely small FWHM, making it highly promising in the field of organic optoelectronic functional materials. However, compared to traditional TADFs with long-range charge transfer (LRCT), MR-TADF materials often suffer from larger... Small singlet-triplet spin-orbit coupling (SOC) exhibits a slower reverse intersystem crossing rate (k). RISC 10 3 -10 4 s -1 This typically leads to the accumulation of triplet excitons, causing severe triplet-triplet-state annihilation (TTA), resulting in a significant efficiency roll-off in electroluminescent devices at high brightness, severely limiting their commercial applications. Furthermore, the large rigid planar structure of these boron-nitrogen-doped polycyclic aromatic hydrocarbon structures significantly enhances intermolecular π-π stacking interactions, easily leading to severe aggregation-caused quenching (ACQ) effects. This further reduces the luminescent performance of the material and the color purity of the device, resulting in a significant broadening of the full width at half maximum (FWHM).

[0005] Therefore, developing a new type of MR-TADF material with high efficiency, low roll-off, and high color purity is of great significance for OLED light-emitting technology and is of great value for the further popularization of OLED technology and the commercial application of MR-TADF materials. Summary of the Invention

[0006] In existing MR-TADF material systems, due to the large overlap integral of HOMO-LUMO, the energy difference between singlet and triplet states is significant. The singlet-tritt spin-orbit coupling is relatively large, and the reverse intersystem crossing process is slow, leading to the accumulation of triplet excitons. This causes triplet exciton triplet annihilation and aggregation-induced quenching effects, resulting in a severe efficiency roll-off in electroluminescent devices at high brightness. The purpose of this invention is to provide a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization and its application in the fabrication of organic electroluminescent devices, thereby solving the above problems.

[0007] The present invention discloses a multiple resonance thermally activated delayed fluorescence material based on long-short axis hybridization, the structural formula of which is shown below:

[0008]

[0009] Ar1 is a group represented by one of the following structural formulas.

[0010] ;

[0011] Furthermore, the multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization described in this invention has one of the following structural formulas:

[0012] The organic electroluminescent device prepared using the product of this invention comprises a cathode, an anode, and one or more organic layers between the two electrodes. At least one of the organic layers is an organic light-emitting layer, which is composed of a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization prepared according to this invention as the guest material and PhCzBCz as the host material. The mass doping ratio of the guest material is 5-7%. This electroluminescent device can be used to prepare organic electroluminescent displays or organic electroluminescent lighting sources.

[0013] Furthermore, an embodiment of the present invention provides an organic electroluminescent device, comprising, from bottom to top, a transparent substrate, an ITO conductive thin film (anode), a hole injection layer (HATCN), a hole transport layer (TAPC), an exciton blocking layer (TCTA and mCP), an organic light-emitting layer, an electron transport layer (TmPyPB), an electron injection layer (LiF), and a cathode layer (Al). All functional layers are prepared by vacuum evaporation film deposition process.

[0014] Preferably, some of the organic compounds used in this device are commercially available or prepared according to known literature or patents, and their molecular structures are shown below:

[0015]

[0016] The beneficial effects of this invention are as follows:

[0017] To address the common problems of aggregation-induced quenching, severe efficiency roll-off at high brightness, and the difficulty in simultaneously achieving color purity and reverse intersystem crossing (RISC) rate in existing MR-TADF materials used in OLED applications, this invention proposes a "dual short-axis-long-axis assisted charge transfer" strategy, aiming to significantly accelerate the RISC process without sacrificing color purity. The core of this strategy is to introduce donor-acceptor type long-range charge transfer units with appropriate steric hindrance onto the indole-carbazole bridge within the classical multiple resonance (MR) framework, enabling the molecule to simultaneously possess multiple excited-state characteristics of short-range charge transfer (SR-CT), space charge transfer (TS-CT), and long-range charge transfer (LR-CT). By adjusting the strength of the acceptor and neutral group, additional TS-CT and LR-CT auxiliary channels can be constructed, effectively reducing the singlet-triplet band gap. This enhances spin-orbit coupling, thereby significantly promoting the upconversion of triplet excitons to singlet states. Simultaneously, the distorted molecular conformation effectively restricts intramolecular vibrational relaxation and suppresses nonradiative quenching in aggregated states; while the retained SR-CT component in the MR-TADF framework ensures high fluorescence quantum yield and extremely narrow emission half-width.

[0018] Thanks to the aforementioned synergistic design, organic light-emitting devices (OLEDs) based on this material maintain high efficiency even under high-brightness operating conditions, significantly alleviating the efficiency roll-off and full width at half maximum (FWHM) broadening issues commonly found in traditional MR-TADF devices, while color purity remains unaffected. This strategy provides a simple and effective way to optimize the performance of MR-TADF materials, overcoming the bottleneck of balancing slow RISC speeds and color purity in existing technologies. It also promotes the development of high-efficiency, high-color-purity, and low-roll-off OLED devices, and is of great value for the further popularization and commercial application of organic light-emitting technology. Attached Figure Description

[0019] Figure 1 The diagram shows the structure of the organic electroluminescent device prepared by the present invention. In the diagram, 1 is a transparent substrate, 2 is an ITO anode, 3 is a hole injection layer, 4 is a hole transport layer, 5 is an exciton blocking layer, 6 is an organic light-emitting layer, 7 is an electron transport layer, 8 is an electron injection layer, and 9 is a cathode.

[0020] Figure 2 : UV, fluorescence (298 K), and phosphorescence (77 K) spectra of compound BN-ICzTRZ; as shown Figure 2 As shown, the maximum absorption peak is at 470 nm, and the main emission peak is at 483 nm, which is blue-green light emission, with a full width at half maximum (FWHM) of 21 nm. Reference (Angew. Chem. Int. Ed. 2023, e202316479.) calculates the energies E of singlet level S1 and triplet level T1 using fluorescence and phosphorescence (77 K) peak values.S1 and E T1 The values ​​are 2.58 eV and 2.46 eV respectively. ΔEST is calculated using the formula: ΔEST = E S1 -E T1 The ΔEST of the molecule is 0.12 eV.

[0021] Figure 3 : UV, fluorescence, and phosphorescence spectra (77 K) of compound BN-ICzCN; as shown Figure 3 As shown, the maximum absorption peak is at 466 nm, and the main emission peak is at 476 nm, which is the emission of blue-green light, with a half-width of 20 nm. The energies of S1 and T1 are calculated to be 2.56 eV and 2.43 eV respectively by fluorescence and phosphorescence (77 K) peak values. The ΔEST of the two molecules is calculated to be 0.13 eV.

[0022] Figure 4 : UV, fluorescence, and phosphorescence spectra (77 K) of compound BN-ICzTh; as shown Figure 4 As shown, the maximum absorption peak is at 465 nm, and the main emission peak is at 475 nm, which is the emission of blue-green light, with a half-width of 21 nm. The energies of S1 and T1 are calculated to be 2.56 eV and 2.45 eV respectively by fluorescence and phosphorescence (77 K) peak values. The ΔEST of the two molecules is calculated to be 0.11 eV.

[0023] Figure 5 External quantum efficiency curves of electroluminescent devices prepared from compound BN-ICzTRZ; such as Figure 5 As shown, the maximum external quantum efficiency is 35.0% at a brightness of 100 cd / m². -2 At that time, the external quantum efficiency was 32.6%; the inset shows the electroluminescence spectrum under a driving voltage of 6 V, with the main electroluminescence peak located at 488 nm, emitting blue-green light, and exhibiting high color purity, with a full width at half maximum (FWHM) of 25 nm.

[0024] Figure 6 External quantum efficiency curves of electroluminescent devices prepared from compound BN-ICzCN; such as Figure 6 As shown, the maximum external quantum efficiency is 38.0% at a brightness of 100 cd / m². -2 At that time, the external quantum efficiency was 31.2%; the inset shows the electroluminescence spectrum under a driving voltage of 6 V. The main electroluminescence peak is located at 484 nm, which is green light emission and has high color purity, with a full width at half maximum (FWHM) of 25 nm.

[0025] Figure 7 External quantum efficiency curves of electroluminescent devices prepared from compound BN-ICzTh; such as Figure 7As shown, the maximum external quantum efficiency is 30.1% at a brightness of 100 cd / m². -2 At that time, the external quantum efficiency was 24.4%; the inset shows the electroluminescence spectrum under a driving voltage of 6 V, with the main electroluminescence peak located at 484 nm, emitting green light, and exhibiting high color purity, with a full width at half maximum (FWHM) of 25 nm. Detailed Implementation

[0026] The present invention will be further described below with reference to the accompanying drawings to facilitate understanding by those skilled in the art. Obviously, the described embodiments are only a part of this experiment and not all embodiments. Any non-essential modifications, equivalent substitutions, and improvements made to the present invention by those skilled in the art based on the above description should be included within the scope of protection of the present invention. All raw materials mentioned below are commercially available or prepared according to known literature or patents. Any unmentioned process steps and preparation methods are well-known to those skilled in the art.

[0027] Example 1:

[0028] The preparation steps of BN-ICzTRZ are as follows:

[0029]

[0030] Synthesis of BN-ICzTRZ: Under nitrogen protection, 11,12-dihydroindolo[2,3-a]carbazole (10 mmol, 2.58 g) and cesium carbonate (42.94 mmol, 14 g) were dissolved in 70 mL of DMF. After stirring at room temperature for 30 min, a DMF solution of 2-(4-fluorophenyl)-4,6-diphenyl-1,3,5-triazine (2 g, 6.11 mmol) was added dropwise. The reaction was heated to 140 °C and stirred for 12 h. After cooling to room temperature, the mixture was poured into ice water. The resulting yellow precipitate was collected by filtration, recrystallized from methanol, and dried in a vacuum oven to give intermediate ICz-1. The intermediate, requiring no further purification, was mixed with BNCz-Br (1 mmol, 720 mg), sodium tert-butoxide (2.96 mmol, 291 mg), palladium acetate (Pd(OAc)2, 0.07 mmol, 15 mg), and tri-tert-butylphosphine tetrafluoroborate (tBu3PHBF4, 0.17 mmol, 50 mg) in 20 mL degassed toluene under nitrogen protection. The mixture was heated to 110 °C and stirred for 18 hours. After cooling to room temperature, the reaction mixture was poured into 100 mL of water and extracted with dichloromethane. The organic phase was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography using dichloromethane / petroleum ether (v / v = 1:3) as eluent. The final product was a yellow solid (720 mg, 60% yield, based on BNCz-Br).

[0031] 1 H NMR (500 MHz, Methylene Chloride-d2) δ 9.12 (d, J = 2.0 Hz, 2H), 8.38 (dd, J = 8.1, 5.7 Hz, 2H), 8.30 (dd, J = 15.4, 7.9 Hz, 2H), 8.27 – 8.20(m, 8H), 7.94 (d, J = 2.0 Hz, 2H), 7.82 (s, 2H), 7.61 (dd, J = 8.5, 3.4 Hz, 3H), 7.54 (tt, J = 7.2, 1.3 Hz, 2H), 7.44 – 7.33 (m, 6H), 7.32 – 7.26 (m,2H), 7.24 (d, J = 8.2 Hz, 1H), 7.17 – 7.11 (m, 2H), 6.94 (dd, J = 8.7, 2.1Hz, 2H), 1.62 (s, 18H), 1.23 (s, 18H). 13C NMR (151 MHz, Methylene Chloride-d2) δ 170.99, 170.23, 145.79, 145.25, 145.23, 144.70, 144.21, 143.38, 143.13,141.96, 138.19, 136.29, 134.72, 132.51, 130.09, 130.05, 129.05, 128.74,128.61, 128.39, 127.52, 127.25, 126.40, 126.34, 126.14, 125.99, 125.83,124.37, 124.08, 121.97, 121.77, 121.29, 120.49, 120.43, 117.72, 114.88,114.63, 113.37, 111.59, 111.37, 107.14, 32.30, 31.62. ; MALDI-TOF (m / z) [M+]:1201.994, calcd. 1201.594.

[0032] Example 2:

[0033] The preparation of BN-ICzCN involves the following steps:

[0034]

[0035] Synthesis of ICz-2: Under a nitrogen atmosphere, BNCz-Br (4.17 mmol, 3 g), 11,12-dihydroindolo[2,3-a]carbazole (15 mmol, 3.84 g), sodium tert-butoxide (18.91 mmol, 1.86 g), Pd2(dba)3 (0.15 mmol, 140 mg), and tBu3PHBF4 (1.52 mmol, 440 mg) were dissolved in 100 mL of degassed toluene. The mixture was heated to 110 °C and stirred for 24 hours. After cooling to room temperature, the reaction mixture was poured into 100 mL of water, and the product was extracted with dichloromethane. The solvent was removed under reduced pressure to obtain the crude product, which was then purified by silica gel column chromatography using dichloromethane / petroleum ether (v / v = 1:2) as the eluent. The final product was a deep yellow solid (1.96 g, 50% yield).

[0036] 1H NMR (500 MHz, Methylene Chloride-d2) δ 9.29 (d, J = 1.9 Hz, 2H), 8.69 (s, 2H), 8.62 (d, J = 1.8 Hz, 2H), 8.34 (d, J = 2.0 Hz, 2H), 8.25 – 8.18(m, 7H), 7.53 (t, J = 7.7 Hz, 2H), 7.47 (t, J = 7.3 Hz, 1H), 7.42 (dd, J =8.9, 2.1 Hz, 2H), 7.28 – 7.25 (m, 2H), 1.76 (s, 18H), 1.45 (s, 18H). 13 C NMR(151 MHz, Methylene Chloride-d2) δ 147.49, 146.92, 146.83, 143.03, 139.47,131.30, 128.50, 126.99, 126.48, 126.20, 125.29, 122.66, 122.08, 121.46,121.14, 121.04, 118.89, 115.19, 114.44, 113.73, 112.45, 111.44, 108.09,55.10, 54.92, 54.74, 54.56, 54.38, 33.24, 33.03, 32.97, 32.71.; MALDI-TOF (m / z) [M+]:894.715, calcd. 894.483.

[0037]

[0038] Synthesis of BN-ICzCN: Under a nitrogen atmosphere, ICz-2 (1.21 mmol, 1.08 g), 4-bromobenzonitrile (1.2 mmol, 0.22 g), sodium tert-butoxide (5.92 mmol, 582 mg), Pd(OAc)2 (0.12 mmol, 30 mg), and tBu3PHBF4 (0.34 mmol, 100 mg) were dissolved in 50 mL of degassed toluene. The mixture was heated to 110 °C and stirred for 18 hours. After cooling to room temperature, the reaction mixture was poured into 100 mL of water, and the product was extracted with dichloromethane. The solvent was removed under reduced pressure to give the crude product, which was then purified by column chromatography using dichloromethane / petroleum ether (v / v = 1:1) as the eluent. The final product was a yellow solid (501 mg, yield 42%).

[0039] 1 H NMR (500 MHz, Methylene Chloride-d2) δ 9.21 (d, J = 1.6 Hz, 2H), 8.55 (d, J = 1.4 Hz, 2H), 8.32 (d, J = 6.1 Hz, 4H), 8.28 (d, J = 1.7 Hz, 2H), 7.82 (d, J = 9.2 Hz, 3H), 7.75 (d, J = 7.1 Hz, 2H), 7.46 – 7.41 (m, 2H), 7.38 (t, J = 5.9 Hz, 1H), 7.27 – 7.18 (m,3H), 7.10 – 6.93 (m,5H), 1.70 (s, 18H),1.43(s, 18H). 13 C NMR (151 MHz, Methylene Chloride-d2)) δ 145.70, 144.55,143.93, 138.27, 129.86, 129.48, 128.30, 127.12, 124.74, 124.22, 123.85,120.99, 117.35, 116.75, 114.22, 109.60, 108.63, 35.23, 34.84, 32.20, 32.05,31.82; MALDI-TOF (m / z) [M+]:995.829, calcd. 995.510.

[0040] Example 3:

[0041] The preparation of BN-ICzTh involves the following steps:

[0042]

[0043] Synthesis of BN-ICzTh: 11-(dibenzo[b,d]thiophene-2-yl)-11,12-dihydroindolo[2,3-a]carbazole (1.50 mmol, 0.66 g) was dissolved in 20 mL of degassed toluene under nitrogen protection with BNCz-Br (1.11 mmol, 800 mg), sodium tert-butoxide (2.96 mmol, 291 mg), Pd(OAc)2 (0.07 mmol, 15 mg), and tBu3PHBF4 (0.17 mmol, 50 mg). The mixture was heated to 110 °C and stirred for 18 hours. After cooling to room temperature, the reaction mixture was poured into 100 mL of water and extracted with dichloromethane. The organic phase was concentrated under reduced pressure, and the residue was purified by silica gel column chromatography using dichloromethane / petroleum ether (v / v = 1:5) as eluent. The final product was a yellow solid (596 mg, yield 53%, based on BNCz-Br).

[0044] 1H NMR (500 MHz, Methylene Chloride-d2) δ 9.00 (d, J = 1.5 Hz, 1H),8.83 (d, J = 1.6 Hz), 8.51 (d, J = 1.4 Hz, 1H), 8.45 (d, J = 1.5 Hz, 1H),8.36 – 8.29 (m,4H), 8.22 (d, J = 1.4 Hz, 1H), 7.97 (d, J = 7.0 Hz, 1H), 7.86(s, 1H), 7.67 (dd, J = 7.8, 2.0 Hz, 2H), 7.55 (d, J = 1.7 Hz,1H), 7.43 – 7.31(m, 6H), 7.25 – 7.17 (m, 2H), 7.10 (d, J = 6.6 Hz, 1H), 7.00 (t, J = 6.1 Hz,1H), 6.96 (dd, J = 6.7, 1.7 Hz, 1H) 6.90 – 6.85 (m, 3H), 6.70 (t, J = 6.0 Hz,1H), 1.72 (d, J = 4.7 Hz, 18H), 1.51(s, 9H), 1.38(s, 9H). 13C NMR (151 MHz,Methylene Chloride-d2) δ 172.05, 159.01, 146.71, 146.61, 146.50, 146.09,145.21, 144.29 (d, J = 7.8 Hz), 137.37, 135.51, 133.52, 132.51, 131.82,130.74, 130.02, 129.75, 127.94, 127.25, 127.14, 126.81, 126.67, 126.54,125.40, 125.23, 122.75, 122.55, 121.25, 118.53, 118.45, 115.55, 115.27,114.38, 112.38, 112.16, 109.01, 107.78, 33.05, 32.60, 32.43.; MALDI-TOF (m / z)[M+]:1076.666, calcd. 1076.502.

[0045] The technical effects and advantages of the present invention are demonstrated and verified by specifically applying the compounds of the present invention to organic electroluminescent devices and testing their actual performance.

[0046] Example 1: Fabrication of the organic electroluminescent device BN-ICzTRZ

[0047] The technical effects and advantages of this invention are demonstrated and verified by specifically applying the compounds of this invention to organic electroluminescent devices and testing their actual performance. The specific device fabrication process and device performance testing experiments are as follows: The device fabrication process is as follows: Preparation of the ITO glass substrate (a layer of ultrathin ITO conductive film is vacuum sputtered onto a hard glass substrate, serving as the transparent substrate and anode of the organic electroluminescent device); The ITO glass substrate is sequentially cleaned with deionized water, isopropanol, acetone, toluene, acetone, and isopropanol in an ultrasonic bath for 20 minutes each, and then dried in an oven; After surface treatment of the ITO glass substrate coated with the ITO conductive film in an ultraviolet ozone cleaner for 40 minutes, it is transferred to a vacuum evaporation equipment (cavity pressure < 2 × 10⁻⁶). -4 On the ITO conductive film, a hole injection layer HATCN with a thickness of 6 nm is deposited by evaporation; on HATCN, a hole transport layer TAPC with a thickness of 30 nm is vacuum-deposited; on TAPC, an exciton blocking layer TCTA with a thickness of 5 nm is deposited by evaporation; on TCTA, an exciton blocking layer mCP with a thickness of 5 nm is deposited by evaporation; on mCP, an organic light-emitting layer with a thickness of 20 nm is deposited by evaporation; on the organic light-emitting layer, an electron transport layer TmPyPB with a thickness of 40 nm is deposited by evaporation; on TPBi, an electron transport layer LiF with a thickness of 1 nm is deposited by evaporation; on LiF, a cathode Al with a thickness of 100 nm is deposited by evaporation.

[0048] The structure of the organic electroluminescent device BN-ICzTRZ is as follows: ITO / HATCN (6 nm) / TAPC (30 nm) / TCTA (5 nm) / mCP (5 nm) / EML (20 nm) / TmPyPB (40 nm) / LiF (1 nm) / Al (100 nm), where EML represents the organic light-emitting layer, which is composed of 95% by mass of the host material PhCzBCz and 5% by mass of the guest light-emitting material BN-ICzTRZ.

[0049] A DC voltage was applied to the organic electroluminescent device BN-ICzTRZ prepared in this embodiment, and its luminescent performance was evaluated using a Spectrascan PR655 luminance meter. The current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescent characteristics, the electroluminescence spectrum, full width at half maximum (FWHM), CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), and maximum luminance (cd / m²) were measured as a function of the applied DC voltage. 2Detailed electroluminescence performance data of the device are listed in Table 1. The measured values ​​of the fabricated device are: spectral peak value of 488 nm, full width at half maximum (FWHM) of 25 nm, CIE color coordinates of (0.08, 0.33), maximum power efficiency of 47.0 lm / W, and maximum luminance of 23166 cd / m². 2 The maximum external quantum efficiency is 35.0%. At a brightness of 100 cd / m², 2 At that time, the external quantum efficiency was 32.6%.

[0050] Example 2: Fabrication of the organic electroluminescent device BN-ICzCN

[0051] The preparation method is the same as that of Example 1, except that the guest light-emitting material BN-ICzTRZ used in the organic light-emitting layer is replaced with BN-ICzCN. The specific device structure is as follows: ITO / HATCN (6 nm) / TAPC (30 nm) / TCTA (5 nm) / mCP (5 nm) / EML (20 nm) / TmPyPB (40 nm) / LiF (1 nm) / Al (100 nm), where EML represents the organic light-emitting layer. The organic light-emitting layer is composed of 95% by mass of the host material PhCzBCz and 5% by mass of the guest light-emitting material BN-ICzCN.

[0052] A DC voltage was applied to the organic electroluminescent device BN-ICzCN prepared in this embodiment, and its luminescent performance was evaluated using a Spectrascan PR655 luminance meter. The current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescent characteristics, the electroluminescence spectrum, full width at half maximum (FWHM), CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), and maximum luminance (cd / m²) were measured as a function of the applied DC voltage. 2 Detailed electroluminescence performance data of the device are listed in Table 1. The measured values ​​of the fabricated device are: spectral peak value of 484 nm, full width at half maximum (FWHM) of 25 nm, CIE color coordinates of (0.09, 0.29), maximum power efficiency of 45.0 lm / W, and maximum luminance of 17669 cd / m². 2 The maximum external quantum efficiency is 38.0%. At a brightness of 100 cd / m², 2 At that time, the external quantum efficiency was 31.4%.

[0053] Example 3: Fabrication of the organic electroluminescent device BN-ICzTh

[0054] The preparation method is the same as that of Example 2, except that the guest light-emitting material BN-ICzTRZ used in the organic light-emitting layer is replaced with BN-ICzTh. The specific device structure is as follows: ITO / HATCN (6 nm) / TAPC (30 nm) / TCTA (5 nm) / mCP (5 nm) / EML (20 nm) / TmPyPB (40 nm) / LiF (1 nm) / Al (100 nm), where EML represents the organic light-emitting layer. The organic light-emitting layer is composed of 93% by mass of the host material PhCzBCz and 7% by mass of the guest light-emitting material BN-ICzTh.

[0055] A DC voltage was applied to the organic electroluminescent device BN-ICzTh prepared in this embodiment, and its luminescent performance was evaluated using a Spectrascan PR655 luminance meter. The current-voltage characteristics were measured using a computer-controlled Keithley 2400 digital source meter. As luminescent characteristics, the electroluminescence spectrum, full width at half maximum (FWHM), CIE color coordinates, external quantum efficiency (%), power efficiency (lm / W), and maximum luminance (cd / m²) were measured as a function of the applied DC voltage. 2 Detailed electroluminescence performance data of the device are listed in Table 1. The measured values ​​of the fabricated device are: spectral peak value of 484 nm, full width at half maximum (FWHM) of 25 nm, CIE color coordinates (0.09, 0.26), maximum power efficiency of 39.7 lm / W, and maximum luminance of 22597 cd / m². 2 The maximum external quantum efficiency is 30.1%. At a brightness of 100 cd / m², 2 At that time, the external quantum efficiency was 24.4%.

[0056] Table 1: Data parameters of electroluminescent devices provided in the effect examples

[0057]

[0058] As shown in Table 1, the use of materials of this type (BN-ICzTRZ, BN-ICzCN and BN-ICzTh) with certain strength donor and acceptor in the short axis can improve device efficiency while ensuring the full width at half maximum (FWHM) of the device, effectively suppress the roll-off of the device at high brightness, and achieve high-efficiency narrow-band emission.

[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization, the structural formula of which is shown below: Ar1 is a group represented by one of the following structural formulas. 。 2. The multiple resonance thermally activated delayed fluorescence material based on long-short axis hybridization as described in claim 1, characterized in that: Its structural formula is shown in one of the following examples. 。 3. The application of the multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization as described in claim 1 or 2 in the fabrication of organic electroluminescent devices.

4. The application of the multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization as described in claim 3 in the fabrication of organic electroluminescent devices, characterized in that: The organic electroluminescent device consists of a cathode, an anode, and one or more organic layers between the two electrodes. At least one of the organic layers is an organic light-emitting layer, and the organic light-emitting layer is composed of a multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization prepared according to claim 1 or 2 as the dopant material and PhCzBCz as the dopant host material. The mass doping ratio of the dopant material is 5-7%.

5. The application of the multi-resonance thermally activated delayed fluorescence material based on long-short axis hybridization as described in claim 4 in the fabrication of organic electroluminescent devices, characterized in that: This electroluminescent device is used to fabricate organic electroluminescent displays or organic electroluminescent lighting sources.